THEORIES & PRACTICE. - Kohler, E. L. (The Accounting Review, 1940)
The article focuses on theories and practices of accounting. For two decades, accounting processes of the Federal government have drifted along without leadership and with no central guiding principle. Papers, which appeared in the March 1940 issue of journal, The Accounting Review, amply indicated the dissatisfaction of those who have carefully investigated existing practices. There are many persons familiar with Federal accounting to whom the idea of following the commercial pattern is somewhat repugnant. Government is organized for service, not for profit. But costs are the same everywhere and government stands to gain if the well-developed notions of cost accountants can be adapted to the Federal picture. The balance sheet of a Federal department, commission, or other agency need not differ from that of a private corporation, except for the net worth section; yet a number of Federal establishments cannot produce a balance sheet, notwithstanding their ownership and use of various sorts of assets.